Isotopic evidence for dominant secondary production of HONO in near-ground wildfire plumes - J. Chai; J. Chai; J. E. Dibb; B. E. Anderson; C. Bekker; C. Bekker; D. E. Blum; D. E. Blum; E. Heim; C. E. Jordan; C. E. Jordan; E. E. Joyce; et al. (Atmospheric Chemistry and Physics, 2021)
Nitrous acid (HONO) is an important precursor to hydroxyl radical (OH) that determines atmospheric oxidative capacity and thus impacts climate and air quality. Wildfire is not only a major direct source of HONO, it also results in highly polluted conditions that favor the heterogeneous formation of HONO from nitrogen oxides (NOx= NO + NO2) and nitrate on both ground and particle surfaces. However, these processes remain poorly constrained. To quantitatively constrain the HONO budget under various fire and/or smoke conditions, we combine a unique dataset of field concentrations and isotopic ratios (15N /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="93e47eb16cb371fe6916d3191efc4f1d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13077-2021-ie00001.svg" width="8pt" height="14pt" src="acp-21-13077-2021-ie00001.png"/></svg:svg> 14N and 18O /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="fb147fccdcf98a9911cf3d26a8f6dc33"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13077-2021-ie00002.svg" width="8pt" height="14pt" src="acp-21-13077-2021-ie00002.png"/></svg:svg> 16O) of NOx and HONO with an isotopic box model. Here we report the first isotopic evidence of secondary HONO production in near-ground wildfire plumes (over a sample integration time of hours) and the subsequent quantification of the relative importance of each pathway to total HONO production. Most importantly, our results reveal that nitrate photolysis plays a minor role (<5 %) in HONO formation in daytime aged smoke, while NO2-to-HONO heterogeneous conversion contributes 85 %–95 % to total HONO production, followed by OH + NO (5 %–15 %). At nighttime, heterogeneous reduction of NO2 catalyzed by redox active species (e.g., iron oxide and/or quinone) is essential (≥ 75 %) for HONO production in addition to surface NO2 hydrolysis. Additionally, the 18O /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="62d2c8208bbdf49afb8db19c9f7b6b50"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13077-2021-ie00003.svg" width="8pt" height="14pt" src="acp-21-13077-2021-ie00003.png"/></svg:svg> 16O of HONO is used for the first time to constrain the NO-to-NO2 oxidation branching ratio between ozone and peroxy radicals. Our approach provides a new and critical way to mechanistically constrain atmospheric chemistry and/or air quality models on a diurnal timescale.